A study on structural analysis of composite beam structure. (2021) - Robinson, P.; Vishwanath, K.H.; Ashwini, M.V.
Abstract: The active damping of structures is an important emerging field. In this context, it is necessary to be able to develop new control methods for flexible structures and simulate their effects. In order to be able to deal with the optimization of active device locations, spill over and any other general problems linked to control and model reduction, a simple but sufficiently rich model is very useful. This is the reason why this technical note deals with the modelling and simulation of the active vibration control of beam structures using piezoelectric actuators and sensors. Present technology uses the thermal mechanical properties of certain materials which exhibits certain special properties during stresses and by electrical application. Vibrations are the main cause of cyclic failure of structures. This can be reduced by these special devices. In the present study an analysis is carried out to find the damping characters of piezo electric members and extent of reduction. This particular damping is different materials as it directly depends on natural frequency of the system.